Постать Т. Шевченка на сторінках „Украинской жизни" - Полумисна, О.О. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2006)
В статье сделана попытка классификации материалов, посвященных творчеству Т. Шевченка на страницах журнала „Украинская жизнь" (1912-1917), и сделан вывод о том, что наиболее показательными были публикации, соответствующие следующим рубрикам: биографические, общественно-политические, компаративистские и историко-литературные. An attempt to classify the materials devoted to the creative work of T. Shevchenko published in „Ukrayin-skaya zhyzn" magazine is made in the given article. A conclusion is made that the most characteristic were publications corresponding to such topics as biography, social and political life, comparative, historic and literary investigations.
Keywords: Шевченко; журнал "Украинская жизнь"